2005
DOI: 10.1111/j.1365-2036.2005.02620.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a therapeutic trial of high‐dose rabeprazole on symptom response of patients with non‐cardiac chest pain: a randomized, double‐blind, placebo‐controlled, crossover trial

Abstract: SUMMARYBackground: Therapeutic trials with high-dose lansoprazole and omeprazole have been shown to be sensitive clinical tools for diagnosing patients with gastro-oesophageal reflux disease-related non-cardiac chest pain. Aim: To determine the clinical value of a therapeutic trial of high-dose rabeprazole over 7 days in detecting patients with gastro-oesophageal reflux disease-related non-cardiac chest pain. Methods: Double-blind, randomized, placebo-controlled, crossover study. Patients referred by a cardiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 34 publications
(100 reference statements)
6
65
0
7
Order By: Relevance
“…52 55,56 Conversely, response to PPI treatment in NCCP patients without objective evidence of GERD ranged between 10% and 14%. [56][57][58] However, there are less than a handful of randomized, placebo-controlled trials that evaluated the value of PPI treatment in GERD-related NCCP. 59,60 The results of these studies have not been consistent, and thus far the value of antireflux treatment in GERD-related NCCP remains to be elucidated.…”
Section: Atypical M Anifestations Of Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…52 55,56 Conversely, response to PPI treatment in NCCP patients without objective evidence of GERD ranged between 10% and 14%. [56][57][58] However, there are less than a handful of randomized, placebo-controlled trials that evaluated the value of PPI treatment in GERD-related NCCP. 59,60 The results of these studies have not been consistent, and thus far the value of antireflux treatment in GERD-related NCCP remains to be elucidated.…”
Section: Atypical M Anifestations Of Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…Empirical PPI trial has been shown to be a simple, sensitive, noninvasive, and cost-effective diagnostic test for GERD-related NCCP [11][12][13][14]. OGD in the absence of alarm symptoms (e.g., weight loss, odyngophagia, dysphagia, gastrointestinal bleeding, or anemia) has been shown to provide very little useful information in the initial evaluation of patients with NCCP.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to address which pathophysiologic mechanism is involved before deciding a symptom-based therapy. Esophageal chest pain secondary to GERD responds well to PPI therapy [56], but when ineffective or in those with persistent symptoms, therapeutic options are very limited. Some studies have shown improvement of esophageal sensory thresholds or symptoms of pain with drugs such as selective serotonin reuptake inhibitors (SSRI) (sertraline) [57], NMDA receptor antagonist (ketamine) [24], selective 5-hydroxytryptamine (5-HT) reuptake inhibitors (citalopram) [58], 5-HT4 receptor agonists (tegaserod) [59], and tricyclic antidepressants (imipramine, amitriptyline, or trazodone) [60][61][62].…”
Section: Treatmentmentioning
confidence: 98%